2016
DOI: 10.18632/oncotarget.13378
|View full text |Cite
|
Sign up to set email alerts
|

TSC loss distorts DNA replication programme and sensitises cells to genotoxic stress

Abstract: Tuberous Sclerosis (TSC) is characterized by exorbitant mTORC1 signalling and manifests as non-malignant, apoptosis-prone neoplasia. Previous reports have shown that TSC-/- cells are highly susceptible to mild, innocuous doses of genotoxic stress, which drive TSC-/- cells into apoptotic death. It has been argued that this hypersensitivity to stress derives from a metabolic/energetic shortfall in TSC-/- cells, but how metabolic dysregulation affects the DNA damage response and cell cycle alterations in TSC-/- c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 62 publications
(85 reference statements)
1
12
0
Order By: Relevance
“…In humans, mutations in components of TSC sensitize cells to multiple forms of genotoxic stress (Paterson et al, 1982; Deschavanne and Fertil, 1996; Lee et al, 2007; Pai et al, 2016). Thus, we predicted that the GATOR1 mutants, which have a two to three-fold increase in TORC1 activity, might have a globally diminished ability to respond to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, mutations in components of TSC sensitize cells to multiple forms of genotoxic stress (Paterson et al, 1982; Deschavanne and Fertil, 1996; Lee et al, 2007; Pai et al, 2016). Thus, we predicted that the GATOR1 mutants, which have a two to three-fold increase in TORC1 activity, might have a globally diminished ability to respond to DNA damage.…”
Section: Resultsmentioning
confidence: 99%
“…Hyperactivation of TORC1 has been linked to defects in the DNA damage response in single celled and multicellular organisms (Begley et al, 2004; Feng et al, 2007; Klermund et al, 2014; Pai et al, 2016; Ma et al, 2018; Xie et al, 2018). The observation that meiotic DSBs likely promote the GATOR1 dependent downregulation of TORC1 activity during Drosophila oogenesis, suggested that limiting TORC1 activity may be important to the regulation of meiotic DSB repair.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while we observed an inhibitory effect of chronic everolimus therapy on the secretory activity of TSC monocytes, e.g., for IL-1ß or TNFα ( Figure 2B ), acute mTORC1 inhibition did not cause the same effect. This evidenced that not every consequence of aberrantly high mTORC1 activity in TSC cells could be reversed by the acute inhibition of mTORC1, an observation that is not unprecedented ( 33 ). In this context, it is interesting to consider mTOR-independent effects of TSC loss in human monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mutations in components of TSC sensitize cells to multiple forms of genotoxic stress (Deschavanne & Fertil, 1996;C. H. Lee et al, 2007;Pai et al, 2016;Paterson, Sell, Smith, & Bech-Hansen, 1982). Thus, we predicted that the GATOR1 mutants, which have a two to three-fold increase in TORC1 activity, might have a globally diminished ability to respond to DNA damage.…”
Section: Gator1 Mutant Larvae Are Sensitive To Genotoxic Stressmentioning
confidence: 99%
“…Hyperactivation of TORC1 has been linked to defects in the DNA damage response in single celled and multicellular organisms (Begley, Rosenbach, Ideker, & Samson, 2004;Feng et al, 2007;Klermund, Bender, & Luke, 2014;Ma, Vassetzky, & Dokudovskaya, 2018;Pai et al, 2016;Xie et al, 2018). The observation that meiotic DSBs promote the GATOR1 dependent downregulation of TORC1 activity during Drosophila oogenesis, suggested the low TORC1 activity may be important to the regulation of meiotic DSB.…”
Section: Gator1 and Tsc Promote The Repair Of Meiotic Dsbsmentioning
confidence: 99%